2019
DOI: 10.1371/journal.pone.0212352
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after extracorporeal membrane oxygenation in patients with dialysis-requiring acute kidney injury: A cohort study

Abstract: BackgroundAcute kidney injury (AKI) is a common complication of extracorporeal membrane oxygenation (ECMO) treatment. The aim of this study was to elucidate the long-term outcomes of adult patients with AKI who receive ECMO.Materials and methodsThe study analyzed encrypted datasets from Taiwan’s National Health Insurance Research Database. The data of 3251 patients who received first-time ECMO treatment between January 1, 2003, and December 31, 2013, were analyzed. Characteristics and outcomes were compared be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 41 publications
(40 reference statements)
2
28
0
Order By: Relevance
“…This is not surprising, because AKI, particularly in patients who require dialysis therapy, is an independent risk factor of death for patients receiving ECMO [8]. Chen et al found that the outcomes were worse in ECMO patients who had dialysis requiring AKI than in those with AKI not requiring dialysis [14]. Furthermore, Antonucci et al reported that the use of CRRT was not associated with increased mortality in patients who received ECMO support [15].…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising, because AKI, particularly in patients who require dialysis therapy, is an independent risk factor of death for patients receiving ECMO [8]. Chen et al found that the outcomes were worse in ECMO patients who had dialysis requiring AKI than in those with AKI not requiring dialysis [14]. Furthermore, Antonucci et al reported that the use of CRRT was not associated with increased mortality in patients who received ECMO support [15].…”
Section: Discussionmentioning
confidence: 99%
“…In total, 25 studies detailing 5896 adult patients that reported on the use of RRT and ECMO were included ( Table 1 ) [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Twenty-four studies were observational in nature [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], while one study was a randomised controlled trial (RCT) [ 52 ]. For our quantitative analysis, we included 24 observational studies (5855 patients), while the findings of the RCT were reported separately.…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of male patients across the studies ( Figure S3 ) was 68.2% (95% CI: 64.4–71.9%). After removing the two outliers detected by LOO analysis [ 29 , 31 ], the proportion of males was 67.0% (95% CI: 63.0–70.8%). Pooled proportion of concurrent use of VA-ECMO with RRT from 22 studies ( Figure S4 ) was 71.8% (95% CI: 49.8–89.6%) with a significant publication bias ( P egger = 0.007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the indication for ECMO, the modality of ECMO is adapted for the patient. Veno-venous (VV) ECMO provides only respiratory support, and requires patients to have stable hemodynamics, whereas veno-arterial (VA) ECMO provides dual cardiac and respiratory support [1][2][3][4][5][6][7]. In VA ECMO, the blood bypasses both the heart and lungs.…”
Section: Introductionmentioning
confidence: 99%